The impact of emotion on numerosity estimation - Baker, Joseph M.; Rodzon, Katrina; Jordan, Kerry (Frontiers in Psychology, 2013)
Both time and numerosity can be represented continuously as analog properties whose discrimination conforms to Weber’s Law, suggesting that the two properties may be represented similarly. Recent research suggests that the representation of time is influenced by the presence of emotional stimuli. If time and numerosity share a common cognitive representation, it follows that a similar relationship may exist between emotional stimuli and the representation of numerosity. Here, we provide evidence that emotional stimuli significantly affect humans’ estimation of visual numerosity. During a numerical bisection task, enumeration of emotional stimuli (angry faces) was more accurate compared to enumeration of neutrally valenced stimuli (neutral faces), demonstrating that emotional stimuli affect humans’ visual representation of numerosity as previously demonstrated for time. These results inform and broaden our understanding of the effect of negative emotional stimuli on psychophysical discriminations of quantity.